Simulations reveal variability in exposure to drier conditions during timing of budbreak for tree species of the mixedwood forests of Québec, Canada - Benjamin Marquis (Forestry Research)
Due to climate change, the timing of budbreak is occurring earlier in temperate and boreal tree species. Since the warmer conditions also cause snow to melt earlier in the spring, the hypothesis that bud reactivation of tree species of the mixedwood forests of Québec would occur under drier conditions in the future and that species from the temperate forests with late budbreak would be most exposed to dry conditions was tested. The thermal-time bud phenology model was used to predict the timing of budbreak for early and late species using 300 and 500 growing degree-days as the threshold for the timing of budbreak. Climate data was obtained from four CMIP6 climate models from 1950−2100 for two socioeconomic pathways at two locations, one in the temperate forest and one in the boreal mixedwood forest. Using linear regressions, the anomaly, which results from the difference between the historical mean (1950−1980) and the yearly values in timing of budbreak was predicted by the anomaly in drought index (SPEI) per site, climate model, socioeconomic pathways, and species with early or late budbreak timing. Budbreak is expected to occur earlier in the future, whereas the temporal trends in SPEI remained weak during April and May. When paired with the anomalies in both timing of budbreak and drought index, analyses showed that budbreak could be expected to occur under drier conditions in the future. However, due to differences between climate models, it remains uncertain whether drought stress will begin earlier in the future.